Hybrid Learning: Analysis Of Problems And Learning Tools In The Introduction To Business Course - A, Auliana Farabbanie (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Distance learning had already evolved before the pandemic occurred. Implementing Learning Management Systems began through the SPADA Kemdikbud program, and the pandemic further accelerated the adoption of this platform. The limitations of Learning Management System utilization in several universities for supporting hybrid learning have become one of the challenges in the teaching process. This study aimed to analyse issues in hybrid learning and examine the instructional tools used in Introduction to Business courses at the university level. This study employed a descriptive qualitative method with a case study approach. The research subjects were private universities under the Association of Indonesian Teachers (PGRI) within the East Java region. The research findings indicated that the challenges faced in the hybrid learning process at several universities include material comprehension, internet connectivity, and students' learning environment. The decline in student enrollment at several universities did not contribute to the challenges encountered in the hybrid learning process. Learning tools, including syllabus development and semester lesson plans, must continuously improve and align with the applicable curriculum. Utilising a Learning Management System with enhanced content development can facilitate the effectiveness of hybrid learning..